Body composition and somatotype of the elite of Polish fencers - Sterkowicz-Przybycień, Katarzyna (Array, 2009)
Abstract: The purpose of this study was to determine body composition and somatotype of the male fencers who were grouped by different fencing weapons. Analysis of body composition, with untrained men as background, will update the data necessary for the somatic profiles of fencers. Thirty contestants were examined during the Polish Fencing Championships in 2004. They took part in épée (n=10), foil (n=10) and sabre (n=10). They were aged 23.3±2.9; their length of training was 12.6±2.5 years, with the frequency of training 15.9±3.1 hours per week. In each weapon style there were champions and vice-champions of Poland from the year 2004. Twelve of them were classified among the first fifty contestants according to the D’Escrime International Federation (FIE) ranking. An experienced evaluator performed 10 measurements necessary to designate somatotypes by means of Heath-Carter method and to estimate the percentage of body fat and composition.